Hubungan Pengetahuan, Kebiasaan Sarapan Dan Asupan Zat Gizi Makro Sarapan Dengan Status Gizi Pada Remaja - Ahmad Faridi; Andra Vidyarini; Aditya Yudha Prasetya (JURNAL RISET GIZI, 2023)
Background: Nutritional problems in adolescents can cause other health problems. Adolescents with poor nutritional status tend to have low immune system so they are easily affected by disease, besides this, it can inhibit muscle formation during the growth period, lack of intelligence level. In overweight or obese teenagers, it can increase the risk of cardiovascular disease, coronary heart disease and stroke, and cancer.Objective: To determine the relationship between nutritional knowledge, breakfast habits and breakfast macronutrient intake with the nutritional status of school adolescents at SMAN 74 South Jakarta.Method: This research uses a cross-sectional study design with stratified random sampling technique. The population in this study were students of classes X and XI at SMAN 74 South Jakarta. The sample in this study consisted of 86 respondents from class X and XI students. Data were analyzed using the chi square test.Results: The results of the study showed that there was no significant relationship between nutritional knowledge (p = 0.688), breakfast habits (p = 0.413), and macronutrient intake, energy (p = 0.608), protein (p = 0.608), fat (p =0.593), carbohydrates (p=0.359) with nutritional status.Conclusion: Research shows that there is no relationship between breakfast and the nutritional status of female students, but the quality of nutritional intake is still less than the RDA.